2007
DOI: 10.1103/physrevlett.99.190405
|View full text |Cite|
|
Sign up to set email alerts
|

Atomic Landau-Zener Tunneling in Fourier-Synthesized Optical Lattices

Abstract: We report on an experimental study of quantum transport of atoms in variable periodic optical potentials. The band structure of both ratchet-type asymmetric and symmetric lattice potentials is explored. The variable atom potential is realized by superimposing a conventional standing wave potential of lambda/2 spatial periodicity with a fourth-order multiphoton potential of lambda/4 periodicity. We find that the Landau-Zener tunneling rate between the first and the second excited Bloch band depends critically o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(64 citation statements)
references
References 17 publications
4
60
0
Order By: Relevance
“…However, it has already been shown that an experimental realisation of a Bose-Einstein condensate in a PT -symmetric double-well setup can be achieved by embedding the double well in a partially tilted multi-well structure [31]. These systems are well accessible with today's experimental techniques [38][39][40]. If they are exposed to loss effects they exhibit resonances, which show as functions of the physical parameters changes of their crossing scenarios, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has already been shown that an experimental realisation of a Bose-Einstein condensate in a PT -symmetric double-well setup can be achieved by embedding the double well in a partially tilted multi-well structure [31]. These systems are well accessible with today's experimental techniques [38][39][40]. If they are exposed to loss effects they exhibit resonances, which show as functions of the physical parameters changes of their crossing scenarios, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…IV͒. Relevant to the current topic is also the demonstration of sawtoothlike, asymmetric cold atom potentials by Salger et al ͑2007͒. All these systems are currently employed to effectively steer cold matter on a quantum scale.…”
Section: Hamiltonian Quantum Ratchet For Cold Atomsmentioning
confidence: 99%
“…is the photon wave vector, V 1 denotes the potential depth of the usual standing wave potential and V 2 that of the higher spatial harmonic, generated by the dispersion of multiphoton Raman transitions [16,17]. Figure 1 shows the band structure for such a Fourier-synthesized lattice for V 1 ¼ 5E r and V 2 ¼ 1:6E r used in our experiment, where E r ¼ @ 2 k 2 =2m denotes the recoil energy, for two different values of the relative phase ' between lattice harmonics.…”
mentioning
confidence: 99%
“…For a suitable choice of relative phases and amplitudes of the harmonics, the dispersion relation in the region between the first and second excited Bloch band becomes linear, as known for ultrarelativistic particles. We experimentally demonstrate both the transmission of atoms through a potential barrier for the case of a linear dispersion relation, i.e., Klein tunneling, and the usual reflection of atoms by the barrier for the case of a quadratic, i.e., Schrödinger-like, dispersion in an excited Bloch band.The periodic potential used to Taylor the dispersion of ultracold rubidium atoms is of the form VðzÞ ¼is the photon wave vector, V 1 denotes the potential depth of the usual standing wave potential and V 2 that of the higher spatial harmonic, generated by the dispersion of multiphoton Raman transitions [16,17]. Figure 1 shows the band structure for such a Fourier-synthesized lattice for V 1 ¼ 5E r and V 2 ¼ 1:6E r used in our experiment, where E r ¼ @ 2 k 2 =2m denotes the recoil energy, for two different values of the relative phase ' between lattice harmonics.…”
mentioning
confidence: 99%